2023
DOI: 10.1038/s41419-023-05749-5
|View full text |Cite
|
Sign up to set email alerts
|

Influenza viral matrix 1 protein aggravates viral pathogenicity by inducing TLR4-mediated reactive oxygen species production and apoptotic cell death

Abstract: Influenza virus is one of the most challenging viruses threating human health. Since infection with influenza virus triggers inflammatory responses and induces cell death, the molecular and cellular mechanisms by which the virus-infected cells undergo apoptotic and necrotic cell death have been widely studied. However, most of the studies have focused on the molecular events occurring in the cytosol and there is limited information on the physiological correlation between virus-induced cell death and the viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…NS1 overexpression activates the JNK MAPK signaling pathway in certain influenza virus subtypes [ 41 ]. The M1 protein of the influenza virus induces apoptosis by activating the TLR4 signaling pathway [ 14 ]. Similarly, we found that the overexpression of either influenza NS1 or M1 proteins activated the JNK MAPK signaling pathway, causing a decrease in FcRY expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS1 overexpression activates the JNK MAPK signaling pathway in certain influenza virus subtypes [ 41 ]. The M1 protein of the influenza virus induces apoptosis by activating the TLR4 signaling pathway [ 14 ]. Similarly, we found that the overexpression of either influenza NS1 or M1 proteins activated the JNK MAPK signaling pathway, causing a decrease in FcRY expression.…”
Section: Discussionmentioning
confidence: 99%
“…PB2 protein blocks JAK1/STAT signaling by degrading JAK1, thereby impeding the production of interferon-stimulated genes (ISGs) [ 13 ]. The M1 protein of influenza viruses enhances viral pathogenicity by activating the Toll-like receptor 4 (TLR4) signaling pathway [ 14 ]. These studies suggest that the influenza virus suppresses host antiviral responses by modulating immune signaling through its core proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Viral infection increases ROS production in immune and infected host cells [ 43 ]. For instance, the influenza virus stimulates intracellular ROS overproduction via TLR4 signaling pathway activation, leading to enhanced apoptotic cell death in the lungs [ 44 ]. Innate immune cells produce mtROS for use as antimicrobial agents in the host defense against infectious microorganisms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%